自閉譜系障礙之兒童透過即興劇表達社會情感之個案研究 =: A case study on using drama improvisation as a social emotional intervention for a child with ASD - Wong, On Na; Ho, Ka Lee Carrie (University of Saint Joseph, 2023)
"Abstract The core concept of drama education is the integration and int- ernalization of experience. In the empirical content of the improvis- ational drama, it lays a profound foreshadowing for future life prac- tice through different physical behaviors and facial perceptions. Through drama education, children with autism spectrum disorder can be emotionally adjusted. Emotional and social behavior is essent- ial for children with autism spectrum disorders. The use of improvis- ational drama to study children's emotions with autism spectrum diso- rders is not yet found in Macau. Therefore, this study aimed to inve- stigate the intervention strategies for children with autism spectrum disorders through improvisational drama to fill the research gap. A case study of emotional interventions as a ten-day improvisa- tional drama with an autism spectrum disorder in Macau. The following findings were obtained: 1. The study found that improvisational drama was used to address the theoretica deficits of the mind of children with autism spectrum disorders. 2. Improvisational drama supports the understanding of self-emotions in children with autism spectrum disorder with positive behavior. 3. Shared attention cultivated by improvisational drama can develop social interaction behavior. 4. The improvisational drama techniques can deal with children with autism spectrum disorder and peer conflict. Based on these results, the researcher identified three main is sues in the use of improvisational drama to deal with the emotions of VII children with autism spectrum disorders in Macau: 1. The relative lack of knowledge on the use of improvisational drama as a strategy to support children with autism in Macau. 2. The number of hours and sessions of the Macao training course is too small to be satisfied with frontline teachers' use of improvi- sational drama to provide quality teaching to children with an au- tism spectrum disorder. 3. Failing to understand the emotional needs of children with autism frontline teachers must practice improvisational drama teaching, failing to understand it’s core subjects in depth. Therefore, researchers on the emotions of children with an aut- ism spectrum disorder in improvisational drama. The proposal is divi- ded into three main areas, which are proposed to the government, sch- ools, and teachers: I. Suggestions to the government: 1. Improve the special education policy 2. Increase the number of training courses II. Suggestions for schools: 1. Increase the teaching content of the curriculum for children wi- th autism spectrum disorders III. Suggestions for teachers: 1. Children should lead the curriculum with autism spectrum disord- ers. 2. The curriculum should enhance the cooperation between children VIII with autism spectrum disorders and their peers. This study has identified feasible intervention strategies to he- lp further improve the Macau government's special education policy. The study also aims to help schools to adapt their teaching cont- ents better to suit the needs of children with autism spectrum disord ers. Finally, the study aims to provide teachers with a better unders- tanding of the characteristics and social-emotional behaviors of ch- ildren with autism spectrum disorders to help each other practice education effectively. Only one child with autism spectrum disorder were studied in Mac- ao. As a result, this study failed to represent all children in Macao in practicing emotional interventions in improvisational drama. This study aimed to promote -improvisational comedy strategies in Macau to help children with aut-ism spectrum disorders to understand and expre ss their emotions appr-opriately. It is also expected that the Macau SAR government will re-cognize the importance of drama education for children with autism spectrum disorders and develop policies and ada- pt the content of the curriculum framework to enable the effective i- mplementation of drama education in teaching emotions to children wi- th autism spectrum disorders."
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 即興戲劇; 情緒; 戲劇教育; 自閉譜系障礙兒童

澳門幼稚園老師對幼兒偏差行為的態度及輔導策略 - Cheong, Wai Fan (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門幼兒園教師對推行美感教育的態度=Kindergarten Teachers’ Attitudes Towards the implementation of Aesthetic Education in Macau - Ho, Ka Kio (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門小學教師與資源教師合作現況與挑戰 - Chao, Cheng I. (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

探討透過「五感教學」進行幼兒社交情緒教育之行動研究 =: Action Research on Teaching the Social Emotion in Children by Using on Five-Senses Teaching Approach - Lei Weng I (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

探討澳門托兒所推行融合托兒服務的策略與挑戰 - Fong, Sou Lei (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Who has the power? A reflection on teaching drama improvisation with young children - Ho, Ka Lee Carrie (Journal of Early Childhood Research, 2020)
The following study reflects and explores the dynamics of aesthetic experiences within drama improvisations. This arts-based research was carried out in Hong Kong with six Cantonese children who were aged 3?5?years. Data were collected from the video transcripts of five workshops and the researcher?s own research journal. Two significant milieus were observed: switching in-between roles and intuitive creativity is not talkback. I argue that because each of these two milieus provide the foreground for the complex ? and at times contradictory ? nature of children?s aesthetic experiences where Deleuzian power is at play, opportunities arise for both, challenging the traditional adult?child power relations, and in so doing, educators can be able to reconfigure and reconceptualise teaching goals and practices, both generally and specifically, within the context of early childhood education.

Understanding of base-10 concept and its application: a cross-cultural comparison between Japan and Singapore - Marcruz, Ong Yew Lee; Carrie, Ho Ka Lee; Manabu, Kawata; Mayumi, Takahashi; Kumpei, Mizuno (International Journal of Early Years Education, 2022)
It has become increasingly clear that the early use of decomposition for addition is associated with later mathematical achievement. This study examined how younger children execute a base-10 decomposition strategy to solve complex arithmetic (e.g. two-digit addition). 24 addition problems in two modalities (WA: Written Arithmetic; OA: Oral Arithmetic) with sums less than 100 were administered to 22 Japanese and 22 Singaporean 6-year-old kindergarteners. Our findings reveal that they were able to solve complex addition. For instance, Japanese kindergarteners tended to solve complex arithmetic using base-10 decomposition across the modality, whereas Singaporean kindergarteners used standard algorithms and basic counting to solve complex WA and OA problems, respectively. We speculate that Japanese kindergarteners might have a clearer understanding of the base-10 concept and were able to use this knowledge more readily than Singaporean kindergarteners. Mathematical experiences in kindergarten and number-naming systems have been put forward as two of the crucial contributors for such cross-cultural differences. This study also provides new directions for future research on the understanding of the base-10 concept and its application among young children.
Keywords: Base-10 concept; decomposition strategy; kindergarten; mathematical experiences; number-naming system

Self-perception of primary students with dyslexia in Macao =: 探討澳門小學讀寫困難融合自我探索學習現況及挑戰 - 何素儀 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Relationship between Student Teachers' Beliefs and Practices on Early Chinese Literacy Instruction - Sun, Chunrong; Ho, Ka Lee Carrie (Universal Journal of Educational Research, 2023)
This study explores the relationship between student teachers' beliefs and practices in early Chinese literacy instruction. Semi-structured interviews, classroom observation, and document analysis were conducted with six student teachers during their teaching practices. Findings indicated that the student teachers believed explicitly teaching literacy skills and imperceptible acquisition of literacy abilities through communication and meaning-making processes are essential in Chinese early literacy learning. However, they mainly taught Chinese literacy skills in their practices, which means the student teachers still needed to practice what they preached fully. The study suggests that possible reasons for the discrepancies include 'direct teaching' and 'rote learning' might be much easier for student teachers to design and conduct a lesson. Student teachers have limited abilities and experiences in conducting an ideal lesson, and the kindergarten curriculum and onsite supervisors highly influenced their teaching practices. The findings from this study suggested that more operational activities (such as designing lesson plans and conducting micro-teaching) should be used during pre-service training. Furthermore, the communication of educational beliefs between the university supervisor and the onsite supervisor should be strengthened.

Perspectives on Inclusion - Correia, Ana; Couzens, Donna; Ho, Ka Lee Carrie (University of Saint Joseph, 2019)
In an inclusive education system, educators engage with increasing their understanding of individual differences, especially in regard to learning, and develop and adjust learning and assessment tasks and contexts in ways that make them accessible and appropriate for all students regardless of starting ability levels, interests, learning strengths and weaknesses. In inclusive schools, diverse approaches to learning are valued and all learners are challenged and supported to be successful in their learning goals. Macao has begun the journey to develop an increasingly inclusive education system. This book has been written as the journey is beggining and explores some of the different perspectives twoard inclusion and interpretaions of "inclusive education" within Macao's education systems and the wider community at this time. The main aims of the research presented in this book are to understand the different views and roles of staff in Macao schools and in the wider community. The book raises questions about how inclusion in Macao might unfold and identifies areas where efforts may be needed to progress inclusive education.

LISTENING TO CHILDREN’S IDEAS TO IMPROVE IN LEARNING AND DEVELOPING HIGHER-ORDER THINKING SKILLS THROUGH REFLECTION WITH DAILY DOCUMENTATION - Ae, Young Choi; Ho, Ka Lee Carrie (University of Saint Joseph, 2022)
Listening to children’s voices is still not considered an essential part of education in some schools, including many in Asian countries. The authority of schools and teachers is still highly valued under the continued influence of Confucian Heritage Culture in many Asian schools, including a significant number in Macao. Teachers in international schools in Asian countries often experience some difficulties when communicating with young children because of their low English proficiency and the traditional views supported by many parents who grew up with the Confucian Heritage Culture, which encourages children to be quiet in the classroom to be good listeners. This Action research took fifteen months between two school years, 2018- 2019 and 2019-2020, with two groups of four and five-year-old students in a kindergarten classroom. Documentation posters were created for young children to use the next morning to reflect on their learning. The pedagogy of listening and pedagogical documentation from the Reggio Emilia approach were implemented to discover and record young children’s ideas and interests, work with daily documentation posters, and help them reflect on documentation posters to improve their learning and develop their higher-order thinking skills. Photos and videos, observation notes with the children’s comments, documentation posters, and reflective discussions were used as interventions to collect the children’s ideas and record their learning activities. The children learned to use documentation posters to remember, think, share, and improve their learning. The children’s comments from Learning Centres, recess, and reflective discussions were used to examine their understanding of learning and higher-order thinking skills. During one Pilot Cycle and three structured data collection cycles, the children demonstrated improvement in learning for each learning project and development of their thinking skills both with and without the teacher’s support. The children demonstrated higher-order thinking skills more often from Learning Centres and recess when they had to solve problems. They also demonstrated higher-order thinking skills more often during the whole group reflective discussions than in small group reflections, when a bigger number of children joined or when they had enough time to think. The thinking skills when children were reflecting were observed to concentrate on remembering and understanding as they focused on remembering and sharing the previous day’s work. The children’s other higher-order thinking skills did not show an increase in frequency during reflective discussions. However, the children demonstrated active engagement and a range of higher-order thinking skills when the teacher asked openended questions and provided support and comments to help them to connect their learning to their past experiences. Findings indicated that the children’s learning from each Learning Centre showed change and improvement during their play over time according to their interests, indicated by their material use and comments. The research was limited by its small number of participants within their age group due to convenience sampling and the children’s relatively limited ability to demonstrate higher-order thinking skills. This study has shown how teachers could help children use daily documentation posters to develop their learning and thinking skills by visualizing their ideas and the teacher’s important role in supporting children’s learning with active listening and support in the classroom
Keywords: Bloom’s Taxonomy; Early Childhood Education; Pedagogical Documentation; Reggio Emilia Approach; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph

Exploring Macau Primary School Teachers’ Understanding and Practices of Educational Innovation - Lai, Hoi In (University of Saint Joseph, 2023)
Teaching methods are not enough in today's social environment. By studying the understanding and practice of innovative education by primary school teachers in Macao, we can find a direction to promoting educators' demand for educational innovation. This research aims to understand the attitudes of primary school teachers in Macao toward innovative education, as well as the feasibility and necessity of developing a creative curriculum, through in-depth interviews with the experiences and reactions of primary school teachers in Macao. Simultaneously, encourage primary school teachers in Macao to implement effective and innovative educational methods so that Macao society can rethink the importance of educational innovation. The significance of the research lies in improving teachers' awareness of educational innovation and promoting teachers' understanding of education. In education, innovation includes new teaching theories, methods, techniques, and resources. Therefore, the education innovation is to think about things creatively, and innovation is to do creative things. By interviewing eleven local primary school teachers in Macau, we learned their views on innovative education teaching methods. Although, a limitation of the study is that only a few faculty members were selected, which may not represent the entire primary teacher in Macau. The study draws four main conclusions, the first of which is the view of primary teacher in local education, it can know that Macao primary school teachers understanding and cognition of educational innovation. Though of understanding of Macau’s primary teacher’s attitude in innovation teaching, which can find the feasibility of innovation teaching in Macau. At the same time, understanding of the impact factor in Macau innovation education, it clarifies the main challenging of primary teacher practice innovation teaching in Macau. On the other hand, thought of understanding of teacher’s attitude, we can more understanding the real situation in Macau’s educational innovation and encourage the teacher promoted educational innovation in Macau
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Constructing an aesthetic discourse: Aesthetic education where Daoism meets postmodernism - Ho, Ka Lee Carrie (Education Inquiry, 2022)
Despite the prevalence of aesthetic education as one of the main developmental objectives in curricular worldwide, the mainstream philosophical discourse on its definition is predominately framed by western philosophy due to a paucity of cross-cultural studies on the subject. The article aims to achieve a contemporary understanding of aesthetic education from both the Chinese and Western aesthetic perspectives. Through the lens of postmodernism, the relationship between Daoist aesthetics and the western postmodern aesthetic perspectives, particularly the Deleuzian concept of rhizome, is identified. Both aesthetic perspectives concern de-authorship and promote self-consciousness/self-awareness. The study reconceptualises the functions of aesthetic education with the Chinese aesthetic philosophy that promotes the nurture of better people through benevolence.
Keywords: Aesthetic experiences; Daoism; Deleuze; aesthetic environments; rhizome

An Investigation into Play-Based Educational Support For The Developing Social-Communication Skills in Children with Autism Spectrum Disorder (ASD) in Kindergarten - Cheong, Tânia Guilherme (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Action Research on Drawing Guidance as an Intervention to Improve Chinese Writing of Primary Students with Dyslexia =: 繪畫活動介入引導讀寫障礙學生提升寫作能力之行動研究 - 黃郁羚 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Qualitative Research on Tutors' Attitudes Towards the Implementation of the Emotional Eduation in Macau Nurseries =: 澳門托兒所導師對幼兒情緒教育態度的質性研究 - Chan, Man Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Qualitative Research on The Career Choice, Current Situation and Prospects of Preschool Tutors Working in Nursery Schools and Kindergartens in Mainland China, Taiwan and Macau=: 中國內地、台灣、澳門幼兒導師從事托兒所和幼兒園工作的職業選擇、現況和前景之質性研究 - Lai Ka Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph